2016
DOI: 10.22159/ijpps.2016v8i12.13168
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Analysis of Human Urine for Oxalate Content

Abstract: Objective: In the present communication, development and validation of reverse phase-high performance liquid chromatography method have been carried out for estimation of oxalate content in the urine of human volunteers with recurrent kidney stone disease and healthy status. Methods:The analysis of oxalic acid has been carried out on KYA TECH HiQ Sil C18HS column using a mobile phase of methanol: 0.001 N acetic acid in water (50:50, v/v) with a flow rate of 1 ml/min and detection wavelength, 237 nm.Results: An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the detection of oxalate ions in blood and urine is of great significance for monitoring renal function, assessing the risk of cardiovascular diseases, diagnosing gout, and detecting urinary stone formation. Currently available methods for oxalate ion detection include enzymatic methods [ 12 ], high-performance liquid chromatography (HPLC) [ 13 ], liquid chromatography-tandem mass spectrometry (LC-MS/MS) [ 14 , 15 ], electrochemical methods [ 16 ], fluorescence spectroscopy [ 17 ], ultraviolet-visible spectroscopy (UV-Vis) [ 18 ], and capillary electrophoresis (CE) [ 19 ]. Enzymatic analysis exhibits high selectivity but is limited by the susceptibility of enzyme activity to environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the detection of oxalate ions in blood and urine is of great significance for monitoring renal function, assessing the risk of cardiovascular diseases, diagnosing gout, and detecting urinary stone formation. Currently available methods for oxalate ion detection include enzymatic methods [ 12 ], high-performance liquid chromatography (HPLC) [ 13 ], liquid chromatography-tandem mass spectrometry (LC-MS/MS) [ 14 , 15 ], electrochemical methods [ 16 ], fluorescence spectroscopy [ 17 ], ultraviolet-visible spectroscopy (UV-Vis) [ 18 ], and capillary electrophoresis (CE) [ 19 ]. Enzymatic analysis exhibits high selectivity but is limited by the susceptibility of enzyme activity to environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…The problems related with kidney are the major problem for human beings. The major functions of the kidney are balancing of electrolytes and regulation of water, production of erythrocytes, regulating the acidbase balance, regulation of blood calcium level, and involve the process of gluconeogenesis [1][2][3]. There will be many diseases which can affect the kidney function.…”
Section: Introductionmentioning
confidence: 99%
“…The non-enzymatic techniques for urinary oxalate measurement include high performance liquid chromatography (HPLC) [12], capillary electrophoresis (CE) [13], ion chromatography [14] and gas chromatography [15]. In our research group, we recently developed a new method for indirectly detecting oxalate in the urine based on precipitation of CaOx crystals, called calcium oxalate crystallization index (COCI) [16].…”
Section: Background and Rationalesmentioning
confidence: 99%
“…High-performance liquid chromatography (HPLC); There are many studies demonstrated measurement of oxalate by HPLC technique. One of them is study by Suryavanshi et al [12]. They used reverse phase-HPLC for oxalate analysis.…”
Section: Non-enzymatic Assaysmentioning
confidence: 99%
See 1 more Smart Citation